2008
DOI: 10.1007/s10763-007-9117-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Two Different Instructional Methods Involving Complex Ecological Content

Abstract: Teaching and learning approaches in ecology very often follow linear conceptions of ecosystems. Empirical studies with an ecological focus consistent with existing syllabi and focusing on cognitive achievement are scarce. Consequently, we concentrated on a classroom unit that offers learning materials and highlights the existing complexity rather than following linear conceptions. We developed an educational unit consisting of 14 individual lessons ("ecosystem lake") with the aim of increasing pupils' cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 47 publications
1
18
0
2
Order By: Relevance
“…1) to control for confounding variables (Randler and Bogner 2009). To assess the effect of repeated testing (Keeves 1998) a control group of pupils also has been tested who visited the zoo but did not participate in any treatment (control group).…”
Section: Methodsmentioning
confidence: 99%
“…1) to control for confounding variables (Randler and Bogner 2009). To assess the effect of repeated testing (Keeves 1998) a control group of pupils also has been tested who visited the zoo but did not participate in any treatment (control group).…”
Section: Methodsmentioning
confidence: 99%
“…The first such study, by Randler and Bogner (2009), looked only at the Teaching about complex systems is no simple matter… teacher's effect on student learning outcomes rather than investigating teacher understanding. The researchers found that teachers had a significant influence on the learning outcome irrespective of the treatment or control condition but that some teachers coped better with traditional teaching methods.…”
Section: Research On Teacher's Understanding Of Complex Systemsmentioning
confidence: 99%
“…The trouts were bought from commercial rearing. Afterwards, the students worked on their own in groups of usually two persons in a student-centered manner following typical student-centered learning approaches (see, e.g., Randler & Bogner, 2009;Randler & Hulde, 2007) for about 60 min. In the last 5 min, students again filled in an immediate postquestionnaire while still sitting in the dissection laboratory.…”
Section: Participants and Data Collectionmentioning
confidence: 99%